Joint ICMI/IASE Study: Teaching Statistics in School Mathematics. Challenges - Batanero Bernabeu, Carmen (2013)
The Joint ICMI/IASE Study was organised by the International Commission on Mathematical Instruction (ICMI; www.mathunion.org/ICMI/) and the International Association for Statistical Education (IASE; www.stat. auckland.ac.nz/˜iase/) to address the lack of attention to teaching statistics in schools. Results from this Study were reflected first in the Proceedings of the Joint ICMI/IASE Study Conference held in Monterrey in 2008 (www.ugr.es/˜icmi/iase_study/) and secondly in the Joint ICMI/IASE book that is to be published in the ICMI Study series by Springer. In this Session the main conclusions of this Study and the Study book will be presented.